Some New Correlations of Q-Value with Rock Mechanics Parameters in Underground Oil Storage Caverns - Fang Lin; Hebing Luan; Yanhua Zeng; Zhibin Zhong (Civil Engineering Journal, 2017)
Q-system is a preferred alternative method of rock mass classification for underground oil storage caverns where stable lithological rocks are widely distributed. In this paper, correspondences between important input rock mechanics parameters (friction angle, cohesion, tensile strength, Poisson’s ratio, deformation modulus) and Q values were investigated, thereby bringing convenient to rapidly obtain available parameters when it’s hard to collect measured field data in underground storage projects basically with similar lithology. The proposed correlations were verified through numerical simulation and on-site monitoring measurement. In addition, comparison of different criteria among Q-system and other codes for rock mass classification has been made to help for making a preliminary evaluation of rock mass quality in the practical engineering. Finally, the behaviours of surrounding rock deformations under different Q values were analysed by using FLAC3D code with the calculating parameters suggested in this paper, and the calculation results match well with measured values in situ. Above results will not only guide the construction but also could be relevant to other underground storage engineering under similar geological conditions.